Penerapan Model Pembelajaran Picture and Picture Untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Alam: Indonesia - Ayu Purnamasari; Anggi Fitri; Yundri Akhyar; Zalisman; Parlindungan Simbolon (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This study aims to improve student learning outcomes by using the application of the Picture and Picture learning model in natural science learning. This type of research is Classroom Action Research (PTK). The data were collected using the test method, then the data were analyzed using descriptive statistical analysis techniques and quantitative descriptive analysis. The results of the research on the level of student activity in cycle 2 were optimal, the disciplinary aspects of 18 people (61%) were in a good category, 21 people (75%) were in a good category, 17 people (58%) were in a good category, and create as many as 19 people (64%) in the good category. This shows an increase in student learning outcomes. So it can be concluded that the application of the Picture And Picture learning model can improve the learning outcomes of fifth-grade students at SDIT Raudhaturrahmah Pekanbaru.